Identification of Staphylococcus aureus α‐hemolysin as a protein drug that is secreted by anticancer bacteria and rapidly kills cancer cells. Issue 6 (24th February 2014) - Swofford, Charles A.; St. Jean, Adam T.; Panteli, Jan T.; Brentzel, Zachary J.; Forbes, Neil S.
ABSTRACT Targeted bacterial delivery of anticancer proteins has the ability to overcome therapeutic resistance in tumors that limits the efficacy of chemotherapeutics. The ability of bacteria to specifically target tumors allows for delivery of aggressive proteins that directly kill cancer cells and cannot be administered systemically. However, few proteins have been tested for this purpose. To identify effective molecules, we systematically sorted proteins that have been shown to cause mammalian cell death. The genes for five proteins were selected and cloned into Escherichia coli and Salmonella. Supernatant from cultures of the transformed bacteria was applied to flasks of MCF‐7 mammary carcinoma cells to identify proteins that (1) were expressed, (2) secreted, and (3) rapidly killed cancer cells. Time‐lapse images were taken to visualize mammalian cell morphology. Of the investigated proteins, α‐hemolysin from Staphylococcus aureus (SAH) was the most promising because it was secreted, caused trauma to cellular membranes, and induced oncosis in 18 min. After exposure for 6 h, SAH decreased cell viability by 90%. In comparison, the positive control, Pseudomonas aeruginosa exotoxin A (PEA), required 11 days to achieve a similar effect, when administered at 3, 000 times its LC50. The maximum death rate induced by SAH was calculated to be a reduction in cell viability of 7.1% per min, which was 200‐fold faster than the PEA control. Two proteins, Dermonecrotic Toxin and Phospholipase C were active when extracted from the bacterial cytoplasm but were not secreted. This investigation revealed for the first time SAH as a potent anticancer drug for delivery by bacteria because of its ability to be secreted in a fully functional form and aggressively kill cancer cells. Biotechnol. Bioeng. 2014;111: 1233–1245. © 2014 Wiley Periodicals, Inc.